The establishment of marine cadastre infrastructure in Malaysia from the legal and technical perspectives / Ashraf Abdullah - Abdullah, Ashraf (Institute of Graduate Studies, UiTM, 2018)
Marine cadastre involves the governing of 3R concepts (right, restrictions and responsibility) in the marine area. Legal and technical issues are the most crucial to drive the implementation of marine cadastre. In Malaysia, the use of the National Land Code 1965 is for land cadastre purposes but it does not cover marine situations. The various marine legal matters that currently exist mainly focus on enforcement and do not emphasize marine spatial issues. The current existing provisions, such as the National Land Code 1965, define the terms used and the concept of cadastre in water body situations. However, they do not specifically discuss marine alienation. Furthermore, the current practice of marine space data acquisition also follows the land standard operations, including types of data used and data presentation. This research is to investigate, establish and propose relevant legal and technical aspects for the establishment of a marine cadastre standard of practice in Malaysia. Various methods have been used in the investigation, particularly through literature reviews on the National Land Code 1965 and other related written acts, rules, regulations and procedures. In addition, personal and group interviews and discussions through a formed focus group involving multi stakeholders such as the Department of Survey Malaysia and the Land and Mine Office were carried out…